Analysis of Perceived Severity, Perceived Vulnerability, Attitude, Subjective Norms, and Perceived Behavioral Control on the Intention to Continue Using a Smartwatch, with Age as a Moderating Variable - Grace Intan Karlina Lidia Simanjuntak; Mas Wahyu Wibowo (International Journal Labs, 2026)
Smartwatches are wearable devices that are increasingly used to support health monitoring, physical activity, productivity, and healthy lifestyles. However, the sustained use of smartwatches remains a challenge because not all users continue using these devices over the long term. This study aims to examine the effects of perceived severity, perceived vulnerability, attitude, subjective norms, and perceived behavioral control on users' continuance intention to use smartwatches, with age serving as a moderating variable. The study integrates Protection Motivation Theory (PMT) and the Theory of Planned Behavior (TPB) and adopts a quantitative survey design. Data were collected from 303 smartwatch users in the Greater Jakarta area belonging to Generation Z and Generation Y and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that attitude, subjective norms, and perceived behavioral control have positive and significant effects on users' continuance intention to use smartwatches, whereas perceived severity and perceived vulnerability do not have significant effects. Furthermore, age significantly moderates the relationships between perceived vulnerability and continuance intention, and between perceived behavioral control and continuance intention, but does not moderate the relationships involving perceived severity, attitude, or subjective norms. These findings suggest that the sustained use of smartwatches is driven more by users' positive attitudes, social influences, and perceived behavioral control than by their perceptions of health threats.